Relationship between right atrial dilation and paroxysmal atrial fibrillation in patients with hypertension and chronic obstructive pulmonary disease - A. I. Tarzimanova; E. V. Kazantseva; A. A. Ivannikov; N. K. Ziskina; V. I. Podzolkov (Кардиоваскулярная терапия и профилактика, 2025)
Aim. To assess the relationship between right atrial (RA) dilation and paroxysmal atrial fibrillation (AF) in patients with hypertension (HTN) and chronic obstructive pulmonary disease (COPD).Material and methods. This retrospective cross-sectional study included 369 patients with HTN and COPD, who were divided into 2 following groups: group I — 68 (18,42%) hypertensive patients with COPD and paroxysmal AF; group II (comparison group) — 301 (81,57%) patients with HTN and COPD without arrhythmia.Results. Patients in group I had significantly higher RA area and left atrial (LA) volume index (LAVI) than patients in group II. Multivariate regression analysis revealed that the RA area and LAVI were associated with paroxysmal AF in comorbid patients with HTN and COPD. To assess the relationship between atrial size and paroxysmal AF in patients with HTN and COPD, we developed a mathematical model with the following equation: р=1/(1+e-z)*100%, z=-12,51+0,130*LAVI+0,408*RAA, where p is the probability of having paroxysmal AF (%), RAA — RA area (cm2); LAVI — left atrial volume index (ml/m2). The p-value ≥24% indicates a high probability of paroxysmal AF (area under the ROC curve (AUC) =0,89, sensitivity — 80%, specificity — 77%).Conclusion. RA dilation is associated with paroxysmal AF in patients with HTN and COPD — odds ratio (OR) 1,50; 95% confidence interval: 1,27-1,79.